Reflexões sobre a trilha sonora a partir de Hanslick - Rafael Sodré de Castro (2016)
In his book The beautiful in music", 1854, Hanslick argues that the beauty in music consists of pure contemplation of musical forms, and not of the composers nor the listeners emotion itself. In the musical context, there still remains the perspective that the best conditions for music creation will be when it is not linked to other languages. On the other hand, there is a clear hegemony of the image in the constitution and in the audiovisual thinking process, which can be perceived by a biased plot centered around visual aspects and a sound demand for possessing, arousing, expressing or representing an emotion through the soundtrack. In general terms, this work examines the musical aesthetics in cinema, focusing on sound expression itself and not on the construction of an affective background to movie scenes. Likewise, it verifies the limits of music and dramas connection in movie construction. Film examples and references from philosophy of music were used to verify if both areas can support an equitable relationship that allows musical and dramatical development in a non-dominant way.